2011
DOI: 10.1007/s10560-011-0229-x
|View full text |Cite
|
Sign up to set email alerts
|

Race, Substance Abuse, and Mental Health Disorders as Predictors of Juvenile Court Outcomes: Do They Vary By Gender?

Abstract: Predicting juvenile court outcomes based on youthful offenders' delin quency risk factors is important for the adolescent social work field as well as the juvenile justice system. Using a random sample of 341 delinquent youth from one Midwestern urban county, this study extends previous research by examining if race, substance abuse, and mental health disorders influence important delinquency outcomes (number of court offenses, felony conviction(s), probation supervision length, detention length, and number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…Webster-Stratton andTaylor (2001) found that substance abuse in juveniles often exists simultaneously with CD, undesirable behaviors, and delinquency. Therefore, it is important for children/youth with mental health issues who encounter the juvenile justice system to receive screening for substance abuse and, if needed, referral for treatment (Welch-Brewer et al, 2011).…”
Section: Prevalence Rates Of Mental Health Issues In the Juvenile Jusmentioning
confidence: 99%
See 1 more Smart Citation
“…Webster-Stratton andTaylor (2001) found that substance abuse in juveniles often exists simultaneously with CD, undesirable behaviors, and delinquency. Therefore, it is important for children/youth with mental health issues who encounter the juvenile justice system to receive screening for substance abuse and, if needed, referral for treatment (Welch-Brewer et al, 2011).…”
Section: Prevalence Rates Of Mental Health Issues In the Juvenile Jusmentioning
confidence: 99%
“…In recent years, the female juvenile offender population has grown exponentially (Cauffman, 2004). Although Cauffman found similarities (e.g., poverty, dysfunction family) between male and female juvenile offenders, differences do exist (e.g., Welch-Brewer et al, 2011). For example, female offenders are more likely to have been victims of physical or sexual abuse.…”
Section: Gender Differencesmentioning
confidence: 99%
“…Among delinquent youths, males and females tend to have similar rates of problematic substance use (Welch-Brewer, Stoddard-Dare, & Mallett, 2011). Although research supports the idea that substance use and delinquency are associated for both female and male youths, the two genders have been shown to have different rates of problem behaviors, somewhat different presentations of these behaviors, and different pathways to risk behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, it is estimated that one fifth of children in the juvenile justice system have a serious mental health problem, including depression, attention-deficit/hyperactivity disorder, anxiety, substance abuse, bipolar, or trauma (Cocozza & Skowyra, 2000;Welch-Brewer, Stoddard-Dare, & Mallett, 2011). In addition, research on juveniles shows that females have higher rates of mental health problems and poorer outcomes as a result of their mental health than their male counterparts (Cauffman, 2008).…”
Section: Mental Health Risk Factorsmentioning
confidence: 99%